Educational and social class assortative mating in fertile British couples - Krzy anowska, Monika; Mascie-Taylor, C. G. Nicholas (Annals of human biology, 2014)
Abstract Background: Positive assortative mating for education and social position has been widely reported in a number of countries, but very few studies have tested whether or not educational or social class homogamy is related to differential fertility. Aim: This study examined the relationship between educational and social class assortative mating and fertility in a British national cohort. Subjects and methods: The analyses were based on 7452 husband-wife pairs from the British National Child Development Study (NCDS). Results: The mean fertility was 3.22 children per couple; the number of children significantly increased from higher to lower social classes and from the more educated to the less educated. The extent of assortative mating for social class and educational level was related to fertility; as educational assortative mating decreased so did the average number of children, whereas the opposite trend was observed for social class. When assortative mating for education and social class were considered together, educational assortative mating was the more significant predictor of the number of children and educationally homogamous couples had higher fertility independent of their social class assortative mating. Conclusions: The relationship between assortative mating and fertility for education and social class appeared to be acting in the opposite direction.